1974
DOI: 10.1002/jcp.1040830112
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Down's syndrome in tissue culture. I. Growth rates protein contents of fibroblast cultures

Abstract: Skin fibroblast cultures from six patients with Down's syndrome (Trisomy 21) were compared with four i n vitro age-matched normal fibroblast cultures. Growth rates were calculated from increases i n cell number and total protein during exponential growth, early in culture lifetime (less than 20 doublings). The Down's syndrome (D.S.) cultures had a n average population doubling time of 35.6 i 1.1 hours and average mass doubling time of 38.6 i 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
51
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 17 publications
10
51
0
Order By: Relevance
“…Despite the prevalence of imbalanced karyotypes in cancer, in vitro studies of aneuploid cells have not provided decisive evidence that aneuploidy alone can promote tumorigenesis. Trisomic human (Segal and McCoy 1974;Stingele et al 2012) and mouse (Williams et al 2008) cells exhibit decreased proliferation, and cells harboring mutations that promote chromosomal instability (CIN) proliferate either normally (Babu et al 2003;Jeganathan et al 2007;Weaver et al 2007) or more slowly, indicating that aneuploidy is, at best, fitness-neutral. Furthermore, studies in mouse models of CIN and Down syndrome (DS) have demonstrated that these conditions can both promote and inhibit tumorigenesis in vivo (Pfau and Amon 2012).…”
mentioning
confidence: 99%
“…Despite the prevalence of imbalanced karyotypes in cancer, in vitro studies of aneuploid cells have not provided decisive evidence that aneuploidy alone can promote tumorigenesis. Trisomic human (Segal and McCoy 1974;Stingele et al 2012) and mouse (Williams et al 2008) cells exhibit decreased proliferation, and cells harboring mutations that promote chromosomal instability (CIN) proliferate either normally (Babu et al 2003;Jeganathan et al 2007;Weaver et al 2007) or more slowly, indicating that aneuploidy is, at best, fitness-neutral. Furthermore, studies in mouse models of CIN and Down syndrome (DS) have demonstrated that these conditions can both promote and inhibit tumorigenesis in vivo (Pfau and Amon 2012).…”
mentioning
confidence: 99%
“…The possibility exists that the culture condition, necessarily different from a natural environment, may enhance the process of early senescence that is characteristic of DS, [15][16][17] thereby preventing detection of proliferation deficits due to cell cycle alterations. In the current study, we were interested in establishing whether impairment of cell proliferation due to mitogenic signaling defects is a generalized feature of the trisomic condition and whether Ptch1 over expression is a common denominator for cell proliferation impairment in DS.…”
mentioning
confidence: 99%
“…The first studies linking aneuploidy to the decreased fitness of eukaryotic cells were conducted in primary fibroblasts from Down syndrome patients that were shown to proliferate more slowly than euploid control cells in vitro [42]. Moreover, aneuploid embryos are often characterized by slow intrauterinal growth and a lower birth weight.…”
Section: Growth Defect Of Aneuploid Cellsmentioning
confidence: 99%